Analisis Kepuasan Nasabah Pada Sistem ATM Studi Komparasi Antara Bank Muamalat Dan Bank Rakyat Indonesia Kota Gorontalo - Ferawati, Ferawati; Latif, Abdul (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2021)
The purpose of this study was to determine the level of customer satisfaction in using the automated teller machine (ATM) system at Bank Muamalat and Bank Rakyat Indonesia (BRI) in the city of Gorontalo, whether it was in line with expectations or not. In this study, the author uses a qualitative research approach using Rating Scala, which collects data from the results of questionnaires, observations and interviews, the data used are primary and secondary data. Based on the results of the study, it is known that the level of customer satisfaction with each bank, both Bank Muamalat and BRI has its advantages and disadvantages, depending on the convenience of the customers themselves in the transaction process at ATMs. Furthermore, the problems experienced by these customers must be a serious concern for BRI and Bank Muamalat to continue to improve the quality of their services, so that customers do not switch to other banks.